Keragaman Mamalia di Cagar Alam Imogiri Kabupaten Bantul - Dyahning Retno Wati; Susilo Irwanjasmoro (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2025)
The Imogiri nature reserve conservation area is located in Bantul Regency and has an area of 11,822 Ha. The area previously functioned as a production forest dominated by eucalyptus trees (Melaleuca leucadendron), which affected the diversity of animals in it, including mammal diversity. After the area was designated as a Nature Reserve, mammal data collection was only carried out once, in 2016. Updating mammal diversity data and information is needed in the management of conservation areas. The study aimed to determine the types of mammals, diversity, and species richness in the Imogiri nature reserve. Data collection using exploration and camera trap methods. The data generated from November 2024 was inputted into the Gunungan Balai KSDA Application and then continued for data analysis. The analysis used the species diversity index (H') and the mammal species richness index (DMg). The results of the study found five types of mammals, including the Javan porcupine (Hystrix javanica), leopard cat (Prionailurus bengalensis), plaintain squirrel (Callosciurus notatus), asian palm civet (Paradoxurus hermaphroditus), and long-tailed macaque (Macaca fascicularis) with low species diversity values (Shannon-Wiener index 0.584) and moderate species richness values (margalef index 3.206). The encounter of protected mammals, namely the Javan porcupine (Hystrix javanica) and leopard cat (Prionailurus bengalensis), is a new record in the Imogiri Nature Reserve.